(untitled) (Research, Society and Development, 2021)
Introduction: Cateterism is the standard examination for diagnosis of coronary artery disease, aided by clinical history and signs and symptoms, the technique is to locate the site of obstruction, evaluating the functioning of valves and heart, thus planning later on the best intervention. Purpose: to analyze the importance of nursing care in front of cardiac cateterism. Methodology: The research in question is a bibliographic, descriptive and qualitative review, based on articles published in periodicals. Data collection took place in September 2021, including articles that are set out in the criteria for inclusion of the last five years, from 2016 to 2021, in the Portuguese language, made available free of charge in BVS, ScieELO and LILACS banks. Results: This study was based on 10 articles. This study brought important results such as the importance of the nursing team, having great value in the monitoring and monitoring process, because it is responsible for preparing the material beforehand, as well as maintaining monitoring and vigorously acting in the process of preventing injury by observing risk signs. Final considerations: It is concluded that it is of fundamental importance for the rehabilitation of the patient in the care of nurses. Thus, it can be said that early intervention by the nurse is capable of minimizing and reducing staples by improving the comfort and safety of the patient.